(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Laser Surface Hardening (LSH) is an advanced technique applicable to a wide range of metals and alloys in modern industrial manufacturing, including the automotive sector. Among the various laser types used for hardening, CO₂, solid-state Nd: YAG, and fibre lasers have traditionally been the most common. However, with the development of high-power diode lasers (HPDLs), these have increasingly gained prominence in this field. In the LSH process, high-intensity laser radiation is focused on a localized area, rapidly heating and hardening the material's surface. The steep temperature gradients resulting from rapid heating and cooling induce structural transformations within the treated area. Additionally, the phase transformation from austenite to martensite occurs without the need for external cooling, simplifying the process. This review paper outlines the fundamental principles of laser hardening and its advantages over conventional hardening techniques. Key process parameters and influencing factors are discussed, along with a comparative analysis of LSH against other hardening methods. Furthermore, an overview of experimental research in this area is provided, with a particular focus on HPDL-based hardening. Various methods for analysing and evaluating laser-treated surfaces are also examined.